Assessment of the prospect for the use of colloidal silver nanoparticles for inactivation of Helicobacter pylori - N. V. Bogacheva (Scientific Сentre for Family Health and Human Reproduction Problems, 2021)
Background. The growth of antibiotic resistance of Helicobacter pylori, a microorganism significant in the development of gastrointestinal diseases and inflammatory periodontal diseases, makes us think about the search for new approaches to the eradication of the microorganism. One solution to this problem may be to develop immunobiological preparations based on microorganisms inactivated with colloidal silver nanoparticles (CSNPs).The aim. To evaluate the inactivating ability of colloidal silver nanoparticles in vitro and in vivo with respect to H. pylori to determine the possibility of their use in the development of a specific immunobiological preparation.Materials and methods. The study design consisted in sequential execution of  the  steps of synthesis of colloidal silver nanoparticles with an assessment of the conditionality of the prepared preparations; isolating and identifying pure H. pylori culture; inactivation of H. pylori by synthesized silver nanoparticles; evaluation of the result of H. pylori inactivation in vitro and in vivo.Results. The conditionality of the synthesized colloidal silver nanoparticles of size 30  ±  3  nm, obtained using a step-by-step technique, was estimated by electron microscopy. Testing the inactivating activity of CSNPs on H. pylori showed that their effect on the culture for 3 hours at a ratio of volumes of CSNPs and 1:1 culture leads to a gradual decrease in the concentration of the microorganism until its complete death and lack of growth on the fifth passage. During the evaluation of the effect of CSNPs on H. pylori, it was shown that the inactivated culture retains its cultural and tinctorial properties; alters morphological properties and biochemical activity; becomes more sensitive to antibiotics and L. acidophilus; ceases to establish in the body of mice with an immunosuppression condition.Conclusions. Proposed method of synthesis of silver nanoparticles with proven inactivating activity against H. pylori can become a stage of biotechnological process of development of vaccine preparation both on the basis of given microorganism and in complex with CSNPs possessing multilevel antimicrobial effect, antioxidant and immunomodulating activity.